Orientation in the environment like perceiving affordances? Andrzej Lewicki’s account of cognition - Piekarski, Michał; Wachowski, Witold (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The purpose of this article is to present Andrzej Lewicki’s account of cognition as orientation in the environment, comparing it with James J. Gibson’s ecological psychology. To do so, we conduct a comparative analysis of the former’s theory of indicators and the latter’s theory of affordance. The theoretical frame for our study is cognitive ecology, a research tradition characteristic of various studies of cognition, including contemporary ones. This allows us to show that, despite differences in the backgrounds and methodologies of these researchers, Lewicki can be considered one of the pioneers of contemporary ecological trends in cognitive science, although his influence has not been as widespread as that of Gibson. Our analysis proceeds in several steps. We begin with an overview of the biographies, backgrounds, and interests of the two researchers, as well as a brief introduction to cognitive ecology and related terms. Next, we discuss action/value indicators theory and affordances theory. We then compare Lewicki’s and Gibson’s approaches in more detail in terms of their use of similar research heuristics. The article ends with conclusions that go beyond historical issues.
Keywords: affordance; cognitive ecology; ecological psychology; indicator of action; indicator of value; methodological individualism; orientation in the environment; tendency of the organism